The unprecedented 2015/16 Tasman Sea marine heatwave - Eric C. J. Oliver (Nature Portfolio, 2017)
The Tasman Sea experienced an unprecedented marine heatwave in 2015/16, with important ecological impacts. Oliveret al. link this event to warm, southwards flowing waters from East Australia and find that climate change has made these events almost seven times more likely.